Changes in Platelet Function in Preterm Newborns with Prematurity Related Morbidities - Irina Franciuc; Elena Matei; Mariana Aschie; Anca Mitroi; Anca Chisoi; Ionut Poinareanu; Nicolae Dobrin; Andreea Georgiana Stoica; Traian Virgiliu Surdu; Mihaela Manea; Sebastian Topliceanu; Georgeta Camelia Cozaru (MDPI AG, 2022)
Platelet indices represent useful biomarkers to express the thromboembolic status, inflammatory response, and oxidative stress in preterm newborns. Our study presented platelet count and function changes in prematurity-related morbidities such as respiratory distress syndrome, intraventricular bleeding, and anemia of prematurity in preterm newborn cases reported to healthy full-term newborns by flow cytometry and hematological methods. The platelet volume represents the average size of platelets in the blood samples, showing the significantly increased values in preterm newborns compared with healthy full-term newborns due to increasing activated platelet production. Flow cytometric analysis of immature platelet fractions (IPF) made using thiazole orange staining to detect their mRNA content and a glycoprotein (anti-GPIIIa) antibody for platelet gating. CD61-TO expression from premature newborns was significantly lower compared to healthy full-term neonates. Preterm newborn cases with respiratory distress syndrome and a need for respiratory support (RDS+) were characterized by a significantly increased platelet volume and a decreased immature platelet fraction reported in RDS− cases. Evaluating the platelet function in the newborn is difficult because the laboratory methodologies work with small quantities of newborn blood samples. The immature platelet fractions and platelet volume promise to be diagnostic biomarkers for diseases.